Redesign of collagen casings for high quality performance using food grade polysaccharides - Sobanwa, Motolani (2022)
Collagen film (casings) obtained from acid-swollen collagen fibres is widely used as an alternative to natural casings for sausage production. However, collagen casings possess weak properties such as low mechanical properties (tensile strength and stiffness) and thermal stability compared to natural casings. Therefore, there is a need industrially to improve these properties. The main purpose of this work was to study the effects of polysaccharides on the properties of acid-swollen collagen pastes and films as a function of collagen paste concentrations (2.5 %, 3.5 % and 4 %wt/wt). In this work, polysaccharides dispersions: cellulose fibres of different length and waxy (WS) and high amylose (HAS) maize starch granules and molecular solutions: Hydroxypropylmethylcellulose (HPMC), Methylcellulose (MC), high molecular weight (GH), low molecular weight guar gum (GM) and Carboxymethylcellulose (CMC) were blended with acid-swollen collagen paste to fabricate collagen films with improved properties such as mechanical properties (tensile strength, stiffness and flexibility) and thermal stability. The viscoelastic of the blend pastes and denaturation of collagen was studied by rheological and thermal techniques. The pure and composite films were studied by sorption, mechanical, spectroscopic, structural, and thermal techniques.